Cathepsin B p.Gly284Val Variant in Parkinson's Disease Pathogenesis - Milanowski, Lukasz M; Hou, Xu; Bredenberg, Jenny M; Fiesel, Fabienne C; Cocker, Liam T; Soto-Beasley, Alexandra I; Walton, Ronald L; Strongosky, Audrey J; Faroqi, Ayman H; Barcikowska, Maria; Boczarska-Jedynak, Magdalena; Dulski, Jaroslaw; et al. (International journal of molecular sciences, 2022)
Parkinson's disease (PD) is generally considered a sporadic disorder, but a strong genetic background is often found. The aim of this study was to identify the underlying genetic cause of PD in two affected siblings and to subsequently assess the role of mutations in Cathepsin B (CTSB) in susceptibility to PD. A typical PD family was identified and whole-exome sequencing was performed in two affected siblings. Variants of interest were validated using Sanger sequencing. CTSB p.Gly284Val was genotyped in 2077 PD patients and 615 unrelated healthy controls from the Czech Republic, Ireland, Poland, Ukraine, and the USA. The gene burden analysis was conducted for the CTSB gene in an additional 769 PD probands from Mayo Clinic Florida familial PD cohort. CTSB expression and activity in patient-derived fibroblasts and controls were evaluated by qRT-PCR, western blot, immunocytochemistry, and enzymatic assay. The CTSB p.Gly284Val candidate variant was only identified in affected family members. Functional analysis of CTSB patient-derived fibroblasts under basal conditions did not reveal overt changes in endogenous expression, subcellular localization, or enzymatic activity in the heterozygous carrier of the CTSB variant. The identification of the CTSB p.Gly284Val may support the hypothesis that the CTSB locus harbors variants with differing penetrance that can determine the disease risk.
Keywords: kathepsin B; heterozygot; fibroblasts; lidé; Genotype; penetrance; Heterozygote; Cathepsin B; Parkinson’s disease; genotyp; Parkinsonova nemoc; CTSB; familial forms; Penetrance; monogenic forms; Parkinson Disease; Humans